2017
DOI: 10.1590/1809-4392201603212
|View full text |Cite
|
Sign up to set email alerts
|

Temporal progress of teak rust in a tropical area of Tocantins State, Brazil

Abstract: Rust, caused by Olivea neotectonae, stands out as the main teak disease, causing premature defoliation regardless of the tree's growth stage. In this study, we aimed to assess the temporal progress of rust in adult teak plants in southern Tocantins State (Brazil). Both rust incidence and severity were evaluated and the disease progress curves were obtained, adjusting to monomolecular, logistic and Gompertz mathematical models. Data from incidence and severity were correlated with climate variables collected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…However, in the months before the beginning of disease progression, such as February and March, there was high rainfall. In this case, the high rainfall combined with the high relative humidity observed before the increase in disease severity in the field favored the establishment of the pathogen in the area, since these conditions contribute to the germination of urediniospores to initiate infection [9]. In turn, the highest mean rainfall, recorded in December, coincided with the lowest mean disease severity.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, in the months before the beginning of disease progression, such as February and March, there was high rainfall. In this case, the high rainfall combined with the high relative humidity observed before the increase in disease severity in the field favored the establishment of the pathogen in the area, since these conditions contribute to the germination of urediniospores to initiate infection [9]. In turn, the highest mean rainfall, recorded in December, coincided with the lowest mean disease severity.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the negative correlation observed between disease severity and monthly mean temperature shows that mild temperatures favor the incidence of fungal sporulation. Sales et al [9] stated that low temperatures can favor the disease because they increase the stress experienced by the plant, thus increasing its susceptibility to the pathogen, since these conditions favor the sporulation of the pathogen. In addition, Ruiz et al [22] observed correlations between the severity of P. psidii in Eucalyptus grandis and temperatures between 18 and 25 • C and high humidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nas plantas infectadas observam-se manchas de coloração marrom escuro (necróticas) na face adaxial da folha e a presença de pústulas amarelas na face abaxial. No campo, a doença pode ocorrer tanto em plantas jovens quanto em plantas adultas, e o principal prejuízo da doença é a desfolha prematura da planta, que pode reduzir em até 30% no crescimento (Sales et al, 2017).…”
Section: Introductionunclassified